A comparative study of Italy’s withdrawal from the Belt and Road Initiative and the Baltic States’ withdrawal from the 17+1 Mechanism - Liu, Juanping (Frontiers in Political Science, 2025)
This article applied MDSD and process-tracing to compare the securitization acts of Italy regarding the Belt and Road Initiative (BRI) and the Baltic States’ withdrawal from the 17+1 Mechanism, analyzing them from the dimensions of driving factors and action pathways. The article finds that the securitization acts of both Italy and the Baltic States were driven by factors such as pressure from allies, ideological differences, geopolitical changes, and economic calculations. However, due to differences in national context and primary threat perception, Italy’s path aligns more closely with a Utilitarian logic, where actions are determined by a calculation of relative economic gains and alliance relationship cost. The Baltic States’ path corresponds more with a logic of ontological security, due to their security reliance on NATO and the Russia–Ukraine war, they emphasized a narrative of ideological confrontation between democracy and authoritarianism in their cooperation with China. In terms of action pathways, Italy engaged in intense political debates over the BRI, the turning point is Draghi government tightened the screening of Chinese investment and technology, then Meloni and members of BOI framed China as existential threat. The Baltic States directly use legislative power to constrict Chinese investment and technology in strategic sectors, and framed China as firm alliance of Russia to pose severe threat to EU’s security and democracy.